The Elusive Agenda: Mainstreaming Women in Development (The Pakistan Development Review, 1996)
A report in 1975 by the International Labour Organisation(ILO) caught world attention by pointing out that while ‘women and girls constitute one-half of the world’s population and one third of the official labour force’ and ‘perform nearly two-thirds of work hours’, they ‘receive only one-tenth of the world’s income and less than one-hundredth of the world’s property.’1 Nearly twenty years later, a report by the United Nations-UNDP’s Human Development Report 1994–found that, despite advances in labour-force participation, education and health, women still constitute about two-thirds of the world’s illiterates, hold fewer than half of the jobs on the market and are paid half as much as men for work of equal value. Women make up only about 10 percent of the world’s parliamentarians and less than 4 percent of cabinet members. The report concludes that ‘in no society are women secure or treated equally’.2